Neuromuscular and motor patterns in breaststroke technique - Conceicao, A.; Silva, A. J.; Barbosa, T.; Campanico, J.; Costa, A.; Louro, H. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2019)
The aim of this study was to analyze the inter-temporal neuromuscular and motor patterns in breaststroke technique. Five national level male swimmers performed 200 m breaststroke at maximal effort. Electromyography data onbiceps brachii, deltoid anterior, pectoralis major and triceps brachiiwere analysed. The relative duration of active and non-active phase and the average rectified value for the neuromuscular patterns were recorded. The swim bouts were videotaped in sagittal plane with a pair of cameras and the Theme software 5.0 was used toanalyse the detected patterns in each swimmer. The neuromuscular pattern revealed that by the average rectified value the biceps brachiiand triceps brachiiwere increased at the end of the test for swimmers 1 and 5, while biceps brachii, deltoid anteriorand pectoralis majorwere increased for swimmers 2 and 4. Different motor patterns between cycles, and between swimmers were observed.We found similarities between the swimmers, adjusting their style to the technical model. The absence of a neuromuscular pattern for all swimmers could be related to different technical models used by each swimmer, as presented in the motor patterns. These findings suggested that each swimmers adapted their own motor and neuromuscular pattern in a unique and distinct way.